Synthesis, Characterization and Anticancer Activity Studies of New Schiff Base Pt (II) Complex - Al-Aghbari, Sama A.; Al-Shuja'a, Omar M.; Al-Badani, Rowaida; Japir, Abd Al-Wali M. (Scientific Research Publishing, 2019)
A New Schiff base ligand and its Pt (II) complex were synthesized. The ligand was prepared by condensation of 2-(4-isobutylphenyl)propanehydrazide with 2,3,4-trihydroxy benzaldehyde this novel ligand and its functional group was carefully designed and selected from well-known biological drugs. The structure of the ligand and its Pt-complex have been confirmed by spectroscopic data, i.e. elemental (CHN) analysis, FT-IR, electronic spectra, NMR spectra. The ligand and its Pt-complex were investigated for their in vitro anticancer potential using HeLa and PC3 cells. The Pt-complex showed a higher cytotoxic activity than the ligand towards Hela cells and PC3 cells.